Complete mitochondrial genome of the Algerian honeybee, Apis mellifera intermissa (Hymenoptera: Apidae). (3rd May 2016) - Hu, Peng; Lu, Zhi-Xiang; Haddad, Nizar; Noureddine, Adjlane; Loucif-Ayad, Wahida; Wang, Yong-Zhi; Zhao, Ren-Bin; Zhang, Ai-Ling; Guan, Xin; Zhang, Hai-Xi; Niu, Hua
Abstract: In this study, the complete mitochondrial genome sequence of Algerian honeybee, Apis mellifera intermissa, is analyzed for the first time. The results show that this genome is 16, 336 bp in length, and contains 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and 1 control region (D-loop). The overall base composition is A (43.2%), C (9.8%), G (5.6%), and T (41.4%), so the percentage of A and T (84.6%) is considerably higher than that of G and C. All the genes are encoded on H-strand, except for four subunit genes ( ND1, ND4, ND4L, and ND5 ), two rRNA genes ( 12S and 16S rRNA ), and eight tRNA genes. The complete mitochondrial genome sequence reported here would be useful for further phylogenetic analysis and conservation genetic studies in A. m. intermissa.